Megalourethra associated with prune-belly syndrome - Gökalp, Ali; Gültekin, E. Yener (The Turkish Journal of Pediatrics, 1993)
A 14-day-old male infant with megalourethra is presented because of the rarity of the anomaly and its association with prune-belly syndrome. The lax, wrinkled appearance of the abdomen, bilateral cryptorchidism and severe dilatation of the urinary system are features included in the classic triad of the prune-belly syndrome. Our patient had the scaphoid variety of megalourethra since the penis appeared elongated and floppy in the fusiform form.
Keywords: megalourethra; prune-belly syndrome; congenital anomaly